Rural Vulnerability and the Ambiguous Legacy of Capitalism: Reassessing the Impact on Countryside Development in the Transition Period to Capitalism - De Keyzer, Maïka (TSEG - The Low Countries Journal of Social and Economic History, 2024)
According to Prak and Van Zanden, land, labor and capital were by the later Middle Ages already primarily allocated through the market. While most scholars have pointed to a century of catastrophes and decline in the eighteenth century, they have focused on the continued growth and market development that took place in this period. While both authors are predominantly urban historians, the countryside plays an important or even defining role in the Dutch evolution toward capitalism. Even though Pioneers of Capitalism provides a wealth of information and points of discussion, I will focus on this aspect in this article.